THE END OF THE WORLD WAR - RADU-ȘTEFAN VERGATTI (Annals: Series on History and Archaeology (Academy of Romanian Scientists))
The end of the world war must be viewed on three fronts: the Italian front, which marked the fall of fascism; the German front, which brought an end to Nazism; and the Japanese front, where Japanese imperialism came to an end. In Italy, the defeat of the Italian Social Republic led Benito Mussolini, along with his lover Claretta Petacci, to seek help from German troops to escape to Switzerland. They were taken aboard into a German convoi. At the edge of the village of Dongo, on the shore of Lake Como, they were stopped by Italian partisans, Mussolini being recongized. Mussolini and Claretta Petacci were arested without any opposition from the Germans. The next day, they were taken from there by a communist partisan who called himself “Colonel Valerio.” Mussolini allegedly promised him “an empire” in exchange for his freedom. However, the partisan summarily executed both Mussolini and Claretta Petacci on the spot. Alongside the bodies of 12 other former Italian officials shot by the communist partisans, their corpses were taken to Milan and publicly displayed, hanging upside down. In this swift manner, fascism in Italy was brought to an end. In Germany, the situation was different. In January 1945, Eisenhower and Churchill urged Stalin to hasten Germany’s defeat. On January 12, 1945, the Soviet offensive for Berlin began. The Soviet army advanced on three fronts: one led by Marshal Zhukov, the second by Marshal Konev, and the third by General Chuikov, the hero of Stalingrad. Faced with this situation, a desperate Hitler ordered on April 26, 1945, that all officers leave Berlin—he wanted to save them. Secondly, he appointed his successors: Goebbels, Admiral Dönitz, and Bormann. Thirdly, decided to commit suicide together with Eva Braun. The next day, he married Eva Braun, and on the third day, inside the Führer’s bunker, Eva Braun took poison and Hitler shot himself. Their bodies were taken by loyal SS soldiers and burned. The following day, Goebbels and his entire family committed suicide. On April 30th, General Krebs proposed a conditional surrender to Soviets, but it was rejected in favor of unconditional surrender. The next day, on May 1, Soviet Sergeant Kantaria entered the Reichstag, climbed to the chapel where the German flag stood, tore it down, and hoisted the Soviet flag as a sign of victory. It was a complete symbol of victory. Berlin had fallen after a devastating and bloody fight. On May 4, 1945, authorized by Admiral Dönitz, Admiral von Friedeburg surrendered to General Montgomery at Lüneburg, along with German forces in northern Germany. On May 7, 1945, Field Marshal Jodl signed the surrender before General Eisenhower in Reims. Following Stalin’s demand, the formal German capitulation was signed in Berlin on May 8, 1945, by representatives of Dönitz’s government. Because the discussions lasted into the night, the final act was signed at 1 a.m. on May 9, 1945. Thus, the Western Allies celebrate Victory in Europe Day on May 8, while the Soviets celebrate it on May 9. Stalin kept his promise to the Western Allies and transferred four Soviet armies to fight the Japanese, who had forces under General Osaka in Manchuria. The Soviet army was commanded by Marshal Vasily Alexandrovich Vasilevsky. It was a total land victory for the Soviets. At the same time, the British, eager to restore their colonial empire, attacked and captured Burma, Rangoon, Siam (Thailand), all of Indochina, Indonesia, and Singapore, and made their fleet available to the Americans. The Americans, after fierce fighting and heavy losses, managed to capture the islands of Iwo Jima and Okinawa. In these conditions, the use of their weppon, the atomic bomb, was considered. The new President of the United States, Harry Truman, declared he would continue the decision of his predecessor, the late President Roosevelt. Generals Marshall and Eisenhower were not fully in agreement. In turn, General Douglas MacArthur, commander of the Pacific forces and thus master of the ocean, was indifferent. As a result, on August 6, 1945, the Japanese city of Hiroshima was bombed, followed by Nagasaki on August 9. The destruction and loss of life were immense. Besides the instantaneous death of hundreds of thousands of people, it became clear that the atomic cloud had deadly effects that could not be fully assessed at the time. Immediately, Emperor Hirohito (1927–1989) convened the Council of Elders, composed of six members. On August 14, 1945, three members of the council voted to continue the war, while the other three voted for surrender. The Emperor decided in favor of surrender. The next day, on August 15, he gave a recorded radio speech in the cryptic language of the imperial court. Very few people understood that he was announcing Japan’s surrender. A group of zealous young officers stormed the Imperial Palace, looking for the speech text and the Emperor to kill him. They failed. The Americans were satisfied, as they had not forgotten Pearl Harbor and wanted revenge. Douglas MacArthur was summoned to sign the act of surrender. This took place on September 2, 1945, aboard the American battleship Missouri. Japan was represented by its foreign minister. As a result, following the signing of the surrender, the Japanese Empire was definitively defeated, and the world war came to a complete end. The signing of peace treaties followed, which will be the subject of another paper. Today, however, although we believed it was left in the past, new influences from that time continue to emerge and shape the present.